Evaluation of the Cytotoxic Effects of Thorn Extracts from Medicinal Plants on the sf21 Cell Line - Malathi, H. (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: The present study was aimed to screen the cytotoxic effect of thorn extracts of seven different plants. Methodology: The methanol extract of thorn of seven different plants were investigated for cytotoxic activity on Sf21 cell line using MTT (3-(4, 5-dimetylthiazol-2-yl)-2 and 5-diphenyltetrazolium bromide) assay. After exposure of the cell line at different concentrations to the plant extract (1.56–500 μg/mL), it was found that percentage of cell viability decreased in dose dependent manner. Results: The extract of Acacia ferruginea showed potential cytotoxic activity with IC50 value of 92.15 μg/mL against Sf21 cell line. Among the studied plants Limonia aciddisima (L), Gymnosporia senegalensis (L), Acacia nilotica and Acacia catechu (L) extracts were exhibited lesser cytotoxic activity, whereas Acacia senegal, Aegel marmelos and Acacia ferruginea were exhibited maximum cytotoxic activity on the Sf21 cell line and these 3 plant extracts has shown potent IC50 value of 188.5 μg/mL, 307.6 μg/mL, 92.15 μg/mL respectively on Sf21 cell lines when compared to control Benzonitrile drug. It is clear from the study that Acacia ferruginea is more cytotoxic to Sf21 cell lines compared to other plant extracts. The GC–MS study of Acacia feruginea showed that it has 37 bioactive components, of which some of the bioactive compounds are methyl mannose (57.14), phenol (8.07), cyclopropane carboxylic acid, benzene-di-carboxylic acid (0.31), hydroxy gamma butyrolactone (0.38), gamma sitosterol (3.52), Hexacosanol (3.83), and stigmasterol (4.65). Conclusion: The bioactive components found in Acacia ferruginia are cytotoxic and insecticidal to other pest. It shows that thorn not only defends themselves against the herbivores, but the specialized bioactive presence also plays a major defensive role. Hence, some of the bioactive can be isolated, characterized, and be used as a potential herbicides.